2011
DOI: 10.1002/sce.20457
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological beliefs of third‐grade students in an investigation‐rich classroom

Abstract: As part of becoming scientifically literate, students should come to appreciate epistemic aspects of science. Little research has been conducted on elementary students' epistemological beliefs specific to science education. This study offers insights into third‐grade students' epistemological beliefs while paying attention to the intersection of epistemological beliefs with instructional context. To document epistemological beliefs, students were interviewed three times during the 5‐month‐long study. To docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…There are so many studies conducted on the epistemological beliefs ( Buehl and Alexander 2001;Dahl et al 2005;Enman and Lupart 2000;Hammer 1994;Havdala and Ashkenazi 2007;Hofer 2001;Hofer and Pintrich 1997;Jehng et al1993;Kardash and Howell 2000;Lee and Tsai 2012;Mason et al 2013;Ravindran et al 2005;Rizk et al2012;Schommer et al 2012;Tolhurst 2007;Tsai 1999;Kittleson 2011;Zinn 2012). The previous research showed considerable evidences that throughout education epistemological beliefs undergo change and become more sophisticated/developed transiting from low grades to high grades (Schommer 1993;Ozdemir and Koksal 2014;Kurt 2009;Yılmaz Tuzun and Topcu 2013;Ogan Bekiroglu and Sengul Turgut 2011;Cano 2005;Tolhurst 2007;De-Juanas and Beltran 2012).…”
Section: Review Of Previous Research Of Epistemological Beliefsmentioning
confidence: 99%
“…There are so many studies conducted on the epistemological beliefs ( Buehl and Alexander 2001;Dahl et al 2005;Enman and Lupart 2000;Hammer 1994;Havdala and Ashkenazi 2007;Hofer 2001;Hofer and Pintrich 1997;Jehng et al1993;Kardash and Howell 2000;Lee and Tsai 2012;Mason et al 2013;Ravindran et al 2005;Rizk et al2012;Schommer et al 2012;Tolhurst 2007;Tsai 1999;Kittleson 2011;Zinn 2012). The previous research showed considerable evidences that throughout education epistemological beliefs undergo change and become more sophisticated/developed transiting from low grades to high grades (Schommer 1993;Ozdemir and Koksal 2014;Kurt 2009;Yılmaz Tuzun and Topcu 2013;Ogan Bekiroglu and Sengul Turgut 2011;Cano 2005;Tolhurst 2007;De-Juanas and Beltran 2012).…”
Section: Review Of Previous Research Of Epistemological Beliefsmentioning
confidence: 99%
“…Fourth, two interview studies were identified that used openended survey questions (Elder, 2002) and open-ended face-to-face interview questions (Kittleson, 2011), which permitted the solicitation of more fine-grained epistemic beliefs about the justification and source of knowledge. These two studies are reviewed next.…”
Section: Personal Epistemology Research On Elementary School Childrenmentioning
confidence: 99%
“…These results demonstrate that elementary school students hold more multifaceted beliefs about the justification and source of knowledge and render the existing, single dimensions of knowledge justification (Hofer & Pintrich, 1997;Schommer-Aikins, 2004) a rather simplistic in their conceptualization. Kittleson (2011) conducted face-to-face interviews with third-grade students (n = 19) over the course of two science lessons in a suburban elementary school in the mid-Atlantic region of the USA. The interviews focused on the four dimensions proposed in Hofer and Pintrich's (1997) framework.…”
Section: Personal Epistemology Research On Elementary School Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…An oft‐stated goal of science education is to support students’ understanding of the nature of science (Deng, Chen, Tsai, & Chai, ), so that they leave school knowing what makes science “science.” Understanding the epistemological basis of science enhances the relevance of science to students in their everyday lives, and, as members of society, enables them to evaluate and draw informed conclusions regarding science‐related issues (Sinatra, Kienhues, & Hofer, ). Moreover, there is a growing body of theoretical and empirical research which contends that there is a close connection between students’ scientific epistemic beliefs (SEB) and various facets of their science learning, such as problem solving and learning strategies (e.g., Bodin, ; Elby, Macrander, & Hammer, ; Kittleson, ; Liang & Tsai, ).…”
Section: Introductionmentioning
confidence: 99%